ANALISIS SENTIMEN MASKAPAI CITILINK PADA TWITTER DENGAN METODE NAÏVE BAYES - Moh Yasid (JURNAL ILMIAH INFORMATIKA, 2019)
The use of airline transportation is no longer a new thing for the community, ranging from business people, families going on vacation, even to the reach of the middle class. This transportation is really needed by the community to be able to travel long distances with a relatively shorter period of time. One of them is Citilink, Citilink is a subsidiary airline of the Garuda Indonesia company with ticket prices that can be reached by the middle class and below. Assessment of Citilink airlines can be seen through any promos that are most promoted to the public. The good and bad services of Citilink Airlines as an evaluation for people who want to use these services, can also be seen from the tweet of the people on Twitter social media. Therefore many researchers use social media as a place to collect data. This research aims to classify or group positive or negative sentiments of the community towards Citilink airline services in order to provide information about public satisfaction with Citilink Indonesia airline services, with a dataset of 2000 tweets resulting in accuracy reaching 0.778, with a processing time of two minutes twenty three seconds.